Non-genetic engineering of cytotoxic T cells to target IL-4 receptor enhances tumor homing and therapeutic efficacy against melanoma. (March 2018) - Gunassekaran, Gowri Rangaswamy; Hong, Chae-Moon; Vadevoo, Sri Murugan Poongkavithai; Chi, Lianhua; Guruprasath, Padmanaban; Ahn, Byung-Cheol; Kim, Ha-Jeong; Kang, Tae Heung; Lee, Byungheon
Abstract: Adoptive transfer of cytotoxic T lymphocytes (CTLs) has been used as an immunotherapy in melanoma. However, the tumor homing and therapeutic efficacy of transferred CTLs against melanoma remain unsatisfactory. Interleukin-4 receptor (IL-4R) is commonly up-regulated in tumors including melanoma. Here, we studied whether IL-4R-targeted CTLs exhibit enhanced tumor homing and therapeutic efficacy against melanoma. CTLs isolated from mice bearing melanomas were non-genetically engineered with IL4RPep-1, an IL-4R-binding peptide, using a membrane anchor composed of dioleylphosphatidylethanolamine. Compared to control CTLs, IL-4R-targeted CTLs showed higher binding to melanoma cells and in vivo tumor homing. They also exerted a more rapid and robust effector response, including increased cytokine secretion and cytotoxicity against melanoma cells and enhanced reprogramming of M2-type macrophages to M1-type macrophages. Moreover, IL-4R-targeted CTLs efficiently inhibited melanoma growth and reversed the immunosuppressive tumor microenvironment. These results suggest that non-genetically engineered CTLs targeting IL-4R have potential as an adoptive T cell therapy against melanoma. Graphical abstract: Image 1